By bread alone : the Bible through the eyes of the hungry - Pilarski, Ahida Calderón; Ngan, Lai Ling Elizabeth; McGinn, Sheila E. (Fortress Press, 2014)
Important ecclesiastical documents have stressed the urgency of world hunger and put in the foreground its natural and historical causes, from famine to global austerity measures and warfare. Here biblical scholars take readings of the Old and New Testaments, exploring the dynamics of hunger and its causation in ancient Israel and the Greco-Roman world and revealing the centrality of hunger concerns to the Bible.